2017
DOI: 10.1080/15548627.2017.1302045
|View full text |Cite
|
Sign up to set email alerts
|

A novel autophagy modulator 6-Bio ameliorates SNCA/α-synuclein toxicity

Abstract: Parkinson disease (PD) is a life-threatening neurodegenerative movement disorder with unmet therapeutic intervention. We have identified a small molecule autophagy modulator, 6-Bio that shows clearance of toxic SNCA/α-synuclein (a protein implicated in synucleopathies) aggregates in yeast and mammalian cell lines. 6-Bio induces autophagy and dramatically enhances autolysosome formation resulting in SNCA degradation. Importantly, neuroprotective function of 6-Bio as envisaged by immunohistology and behavior ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…Further understanding of the mechanisms for α‐synuclein‐autophagy crosstalk in PD might have crucial therapeutic applications. Backing this notion, both in vitro and in vivo studies show that enhancing autophagy and autophagosome‐lysosome fusion could ameliorate PD‐like features by clearing aggregated α‐synuclein (Suresh et al ; Suresh et al ).…”
Section: Autophagy In Pd; Cause and Effect Hand In Handmentioning
confidence: 99%
See 1 more Smart Citation
“…Further understanding of the mechanisms for α‐synuclein‐autophagy crosstalk in PD might have crucial therapeutic applications. Backing this notion, both in vitro and in vivo studies show that enhancing autophagy and autophagosome‐lysosome fusion could ameliorate PD‐like features by clearing aggregated α‐synuclein (Suresh et al ; Suresh et al ).…”
Section: Autophagy In Pd; Cause and Effect Hand In Handmentioning
confidence: 99%
“…Over-expression of a-synuclein also directly compromises macroautophagy through inhibition of Rab1a (Winslow et al 2010). It is also pertinent to note that aggregated a-synuclein in the soma is a key target of treatment strategies in development through induction of macroautophagy (Suresh et al 2017;Suresh et al 2018a).…”
Section: Pink1 and Parkin: Role In Mitophagy And Beyondmentioning
confidence: 99%
“…Toxic protein aggregates and intracellular pathogens are known to be substrates of the autophagy pathway for their effective cellular degradation (Deretic and Levine, 2009 ; Nixon, 2013 ). Based on a previous small molecule screening for aggrephagy inducers from our laboratory (Suresh et al, 2017 ), we identified thiadiazoleacrylamide, XCT 790, as a drug-like molecule that abrogates α-synuclein cellular toxicity, and intracellular Salmonella typhimurium . We tested the potential of XCT 790 to clear toxic α-synuclein protein aggregates, and Salmonella burden through autophagy in mammalian cells such as human neuroblastoma SH-SY5Y and HeLa cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is shown to be dysfunctional during the neurodegenerative disease pathology (Nixon, 2013 ). Thus, restoration of autophagy through pharmacological approaches using small molecules has been reported to be neuroprotective (Sarkar et al, 2007 ; Khurana and Lindquist, 2010 ; Rajasekhar et al, 2015 ; Suresh et al, 2017 ). Small molecule that induces or restores defunct autophagy could aid in toxic aggregate clearance and essential for maintaining the cellular and organismal homeostasis (Rajasekhar et al, 2014 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of the autophagy-lysosomal pathway in the diseased brain has been shown to not only limit intracellular degradation of misfolded SNCA aggregates but also to lead to a detrimental microenvironmental response due to enhanced SNCA secretion, thus promoting PD pathology [ 31 ]. A neuroprotective modulator, 6-Bio, could clear the toxic SNCA aggregates by dramatically enhancing autolysosomal formation in yeast and mammalian cell lines [ 32 ]. Nilotinib, a brain-penetrant tyrosine kinase inhibitor, also facilitates the autophagic clearance of SNCA in transgenic and lentiviral gene transfer models, thus improving the major PD symptoms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%